Restoration of Attention by Rest in a Multitasking World: Theory, Methodology, and Empirical Evidence - Schumann, Frank; Steinborn, Michael B.; Kürten, Jens; Cao, Liyu; Händel, Barbara Friederike; Huestegge, Lynn (Frontiers in Psychology, 2022)
In this work, we evaluate the status of both theory and empirical evidence in the field of experimental rest-break research based on a framework that combines mental-chronometry and psychometric-measurement theory. To this end, we (1) provide a taxonomy of rest breaks according to which empirical studies can be classified (e.g., by differentiating between long, short, and micro-rest breaks based on temporal properties). Then, we (2) evaluate the theorising in both the basic and applied fields of research. Here, we highlight differences between resource-based and satiation-based models, including aspects related to the dynamics and the control (strategic or non-strategic) mechanisms at work. Based on a critical assessment of existing methodological and theoretical approaches, we finally (3) provide a set of guidelines for both theory building and future empirical approaches to the experimental study of rest breaks. We conclude that a psychometrically advanced and theoretically focused research of rest and recovery has the potential to finally provide a sound scientific basis to eventually mitigate the adverse effects of ever increasing task demands on performance and well-being in a multitasking world at work and leisure.